STRATEGI GURU DALAM MENINGKATKAN PERKEMBANGAN KOGNITIF PESERTA DIDIK DI SDN 1 SURANENGGALA KULON - Virren Seky Aursane; Reva Aulia Agustin; Fitra Rahma Dani; Nurkholis (PT. Hasba Edukasi Mandiri, 2025)
This study aims to examine the strategies used by teachers to enhance the cognitive development of students at SDN 1 Suranenggala Kulon. Teachers play a highly significant role in promoting students’ cognitive growth, especially at the elementary school level. This research explores the strategies implemented by teachers at SDN 1 Suranenggala Kulon to improve students' critical, analytical, and creative thinking skills. A qualitative approach was used in this study, involving observation, interviews, and data analysis. The results indicate that active learning methods, integration of interactive learning media, and the adaptation of materials to meet individual student needs are the main effective strategies. This approach not only creates a conducive learning environment but also supports optimal cognitive development.